PROTOCOL OF THE EMG-EXAMINATION OF THE M.MASSETER AND THE M.TEMPORALIS IN BITE HEIGHT REDUCED PATIENTS BY ELECTRONEUROMYOGRAPH “NEURO-EMG-MICRO” - Костишин, А. Б.; Рожко, М. М.; Пелехан, Л. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
It was proposed the version of protocol of the EMG-examination of the m.masseter and the m.temporalis, consider for particularity of clinic bite height reduced symptoms, peculiarity of electroneuromyograph “Neuro-EMG-Micro”, and patients psychological state of health.